SYNTHESIS AND HEAVY-METAL SORPTION STUDIES OF N,N-DIMETHYLACRYLAMIDE-BASED HYDROGELS - Akhmetzhan, Ayatzhan; Abeu, Nurgeldi; Longinos, Sotirios Nik.; Tashenov, Ayezkhan; Myrzakhmetova, Nurbala; Amangeldi, Nurgul; Kuanyshova, Zhanar; Ospanova, Zhanar; Toktarbay, Zhexenbek (MDPI, 2021)
In this work, a hydrogel system was produced via radical polymerization of N,N‐dimethylacrylamide and 2‐acrylamido‐2‐methylpropanesulfonic acid in the presence of N,N‐methylenebis‐acrylamide as a crosslinker and ammonium persulfate as an initiator. Parameters that impact the conversion of copolymerization (such as initial concentration of monomers, temperature, initiator dose, and time) were studied. The swelling degree of the hydrogel was investigated with the addition of a crosslinker and initiator at different pH levels. A hydrogel with high conversion and high swelling degree was selected to investigate their ability for adsorption of Pb(II) ions from solutions. Adsorption behavior of Pb(II) ions in a hydrogel was examined as a function of reaction time and concentration of lead ions from a solution of Pb(II) ions.
Keywords: AMPS; Crosslinker; DMAA; Hydrogel; Metal‐ion adsorption; Swelling ratio; Type of access: Open Access